EKOLOGIS DI TENGAH PANDEMI COVID-19: PENCEMARAN LINGKUNGAN SEBAGAI SUATU MASALAH EKOLOGIS DI MASA PANDEMI COVID-19 - Restifani Cahyami Rosmita (Diegesis : Jurnal Teologi, 2022)
This study aims to explain one of the ecological problems during the Covid-19 pandemic, environmental pollution. This paper was studied using a descriptive qualitative research method based on facts and experiences. This paper shows that environmental pollution in the past has become one of the ecological problems. This is evidenced by paying attention to the surrounding environment where waste due to the pandemic in the form of disposable masks and other health waste that cannot be adequately managed and is disposed of carelessly, causing environmental pollution which has an impact on environmental sustainability and cleanliness and can even lead to natural disasters. Therefore, human ecological awareness is needed at this time, especially in the church, to deal with the Covid-19 pandemic does not lead to the birth of a new ecological problem, namely environmental pollution, but rather a moment of reflection to rebuild a relationship with God through conscious actions of duties and responsibilities toward nature, namely maintaining, managing and working following the mandate given by God.